Synthesis and Characterization of Polysulfone/POSS Hybrid Networks by Photoinduced Crosslinking Polymerization - Dizman, C.; Uyar, T.; Tasdelen, M. A.; Yagci, Y. (Wiley, 2012)
AbstractCrosslinked polysulfone/polyhedral oligomeric silsesquioxane (POSS) hybrid networks were synthesized in this work by photoinduced copolymerization of polysulfone dimethacrylate (PSU‐DMA) and multifunctional POSS‐methacrylamide (POSS‐MAAm) with various feed ratios. The morphology of the nanocomposites was investigated by transmission electron microscopy (TEM), which suggests the random dispersion of POSS in the PSU matrix without macroscopic agglomeration. Thermogravimetric analysis results confirmed that the thermal stability and char yield of PSU‐DMA/POSS‐MAAm nanocomposites increased with the increase of POSS loading. Enhanced glass transition temperatures and storage modulus of the networks were observed to be higher than its precursor polymer.
Keywords: Photopolymerization; Random dispersions; Copolymers; high-performance polymers; Synthesis and characterizations; polysulfone; Thermogravimetric analysis; Polysulfones; Polyhedral oligomeric silsesquioxanes; Copolymerization; Oligomers; nanocomposites; photopolymerizations; Mechanic behavior; crosslinking; Photo-induced crosslinking; Dispersions; High performance polymer; Transmission electron microscopy; polyhedral oligomeric silsesquioxane (POSS); Precursor polymers